Timing Strategies of Direct-Acting Antivirals and Biologics Administration in HCV-Infected Subjects with Inflammatory Bowel Diseases - Imperatore, Nicola; Castiglione, Fabiana; Rispo, Antonio; Sessa, Anna; Caporaso, Nicola; Morisco, Filomena (Frontiers in Pharmacology, 2017)
Background: In the last years, inflammatory bowel disease (IBD) and hepatitis C virus (HCV) infection management has completely changed. However, the role of direct-acting antivirals (DAAs) and the correct timing of antiviral drugs administration in IBD patients needing biologics has not been evaluated. Objective: to discuss the management of HCV-infected IBD patients, focusing our attention on the timing of DAAs administration subjects needing biologics. Methods: Relevant articles addressing HCV management in patients needing biologics were identified by searching from PubMed, MEDLINE and Scopus. Results: Three possible timing strategies were identified: (1) sequential strategy, meaning the choice of treating firstly the active IBD with biologics and then, once the acute phase has been controlled, treating the HCV infection; (2) concomitant strategy, that is the contemporaneous beginning of DAAs and biologics administration; (3) inverted sequential strategy – the administration of antiviral therapy before biologics in HCV-infected IBD patients. The potential pharmacological interactions between biologics and DAAs have also been reported. Conclusions: Clinical management of HCV-infected IBD patients remains a challenging problem for clinicians, especially in terms of timing choice. Recent published data about DAAs are very encouraging also in IBD patients. All strategies could be considered safe and effective. However, further data are immediately required in order to evaluate hepatic toxicity of novel immunosuppressive drugs in IBD.